Responsibility without legal authority? Tackling alcohol-related health harms through licensing and planning policy in local government. - Martineau, F; Graff, H; Mitchell, C; Lock, K (2014)
BACKGROUND: The power to influence many social determinants of health lies within local government sectors that are outside public health's traditional remit. We analyse the challenges of achieving health gains through local government alcohol control policies, where legal and professional practice frameworks appear to conflict with public health action. METHODS: Current legislation governing local alcohol control in England and Wales is reviewed and analysed for barriers and opportunities to implement effective population-level health interventions. Case studies of local government alcohol control practices are described. RESULTS: Addressing alcohol-related health harms is constrained by the absence of a specific legal health licensing objective and differences between public health and legal assessments of the relevance of health evidence to a specific place. Local governments can, however, implement health-relevant policies by developing local evidence for alcohol-related health harms; addressing cumulative impact in licensing policy statements and through other non-legislative approaches such as health and non-health sector partnerships. Innovative local initiatives-for example, minimum unit pricing licensing conditions-can serve as test cases for wider national implementation. CONCLUSIONS: By combining the powers available to the many local government sectors involved in alcohol control, alcohol-related health and social harms can be tackled through existing local mechanisms.